Adult neurogenesis and the microbiota-gut-brain axis in farm animals: underestimated and understudied parameters for improving welfare in livestock farming - Hillerer, Katharina M.; Gimsa, Ulrike (Frontiers in Neuroscience, 2024)
Welfare in commercial livestock farming is becoming increasingly important in current agriculture research. Unfortunately, there is a lack of understanding about the neuronal mechanisms that underlie well-being on an individual level. Neuroplasticity in the hippocampus, the subventricular zone (SVZ), the olfactory bulb (OB) and the hypothalamus may be essential regulatory components in the context of farm animal behaviour and welfare that may be altered by providing environmental enrichment (EE). The importance of pre-and probiotics as a form of EE and the microbiota-gut-brain axis (MGBA) has come under the spotlight in the last 20 years, particularly in the contexts of research into stress and of stress resilience. However, it could also be an important regulatory system for animal welfare in livestock farming. This review aims to present a brief overview of the effects of EE on physiology and behaviour in farm animals and briefly discusses literature on behavioural flexibility, as well as inter-individual stress-coping styles and their relationship to animal welfare. Most importantly, we will summarise the literature on different forms of neural plasticity in farm animals, focusing on neurogenesis in various relevant brain regions. Furthermore, we will provide a brief outlook connecting these forms of neuroplasticity, stress, EE, the MGBA and welfare measures in modern livestock farming, concentrating on pigs.